RELIGIOUS-BASED COMMUNITY AND CONCERN ON MARINE ISSUE: THE PROTESTANT CHURCH OF MALUKU EXPERIENCES - Nancy N. Souisa; Steve G. C. Gaspersz; Fabian N. J. Souisa (Peneliti.net, 2019)
This article focuses on the roles of religious communities within particular social contexts which concern on environmental sustainability. On the one side, it contains a holistic notion, i.e. interconnection of all living fields and living beings with their milieu. It proves that religion's values ​​to communal practices demonstrate a concern for natural sustainability. On the other side, the dynamic of such interest toward environmental sustainability influences a critical exploration and even transformation of religious values. Among religious communities, in Maluku context, the Protestant Church of Maluku (Gereja Protestan Maluku – GPM) is a Christian community that deliberately and systematically struggles on the problem of environmental sustainability by its religious values ​​(Christianity).